Highly Selective Cu-Modified Ni/SiO2–Al2O3 Catalysts for the Conversion of Maleic Anhydride to γ-Butyrolactone in Gas Phase - Bertone, Matías Ezequiel (2015)
The gas phase hydrogenation of maleic anhydride (MA) to succinic anhydride (SA) and the subsequent hydrogenolysis to γ-butyrolactone (GBL) was studied on SiO2-Al2O3-supported Ni catalysts modified with Cu and prepared by incipient wetness impregnation (Ni-I, CuNi-I) and coprecipitation-deposition (CuNi-PD) methods. The samples were characterized by N2 adsorption at -196 ºC, X-ray diffraction, temperature-programmed reduction, transmission electron microscopy and H2 chemisorption. Catalytic tests were performed between 170 and 220 ºC at atmospheric pressure in a fixed bed reactor. Crystalline NiO along with a Ni2+ phase strongly interacting with the support was observed in the oxide precursors. The extent of the strongly interacting Ni2+ phase diminishes according to the following pattern: CuNi-PD > CuNi-I > Ni-I, along with a proportional rise of the NiO phase. The proportion of small to large metal particles, formed after reduction, followed the same pattern as that observed for the extent of Ni2+ phase. All catalysts were very active in the MA hydrogenation to SA, but displayed distinct performances with respect to the subsequent SA hydrogenolysis. Hydrogenolytic activity and GBL yield increased following the same pattern as that obtained for the extent of Ni2+ phase. In addition, the effect of raising temperature on hydrogenolytic activity was more important in the case of Ni-I and CuNi-I than for CuNi-PD. Furthermore, CuNi-PD was more selective to GBL than CuNi-I. These results showed that there is an important effect of Cu addition and preparation method on both the structure and catalytic performance of the metal Ni phase.